Tembikar Baba dan Nyonya: Corak dan Motif Porselin Famille Rose: (Baba and Nyonya Ceramics: Designs and Motifs of the Famille Rose Porcelain) - Grace Choong Ai May (Wacana Seni Journal of Arts Discourse, 2008)
Ceramics are objects of heirloom in Baba and Nyonya families. This paper is a study of the designs and symbolic meanings of motifs found on special Nyonya porcelain ware known as Famille Rose. Famille Rose ware differ from other Chinese ceramics as they are multi-coloured and have special motifs painted on them. Unlike the common blue and white ceramics which were exported from Jingdezhen, Famille Rose porcelain ware were sent to Guangzhou to be painted and then exported from Shanghai for the use of the Straits Chinese. This study shows that several specific motifs such as flowers and animals found on the Famille Rose porcelain ware are connected to the social cultural beliefs of the Baba and Nyonya. Repeated themes which appear on the fine polychrome enamelled porcelain such as bowls, teapots, cups, spoons, and basins include the Phoenix and the Peony.